Analisis Kompetensi dan Penempatan kerja serta pengaruhnya terhadap Motivasi kerja - Mochamad Noval Nasrudin (FADZAT: Jurnal Ekonomi Syariah, 2021)
The purpose of this study was to analyze the simultaneous, partial and dominant influence of competence and job placement variables on work motivation. The research method explains that the location of Lesehan Dapur M'Riah Mojokerto, the type of research is explanatory research, namely research that aims to determine the relationship between two variables of competence and work placement on work motivation. The population of this research is the employees of Lesehan Dapur M'Riah Mojokerto. The number of samples is 30 people, while the data analysis uses multiple linear regression. The results showed that: 1) competence and work placement had a simultaneous effect on work motivation. 2) competence has a partial effect on work motivation and work placement does not partially affect work motivation. 3) competence has a dominant effect on work motivation.